(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article studies the dependence of the biomechanics of motor actions on the physique of athletes in various sports. Numerous examples are given of how the morphological features of athletes, including anthropometric indicators, affect the way technical elements are performed, which ultimately affects the competitive result. The peculiarities of the influence of physique on the biomechanical actions of athletes in such sports as track and field (running, throwing, long jump), weightlifting, powerlifting, swimming are considered. Particular attention is paid to determining the influence of physique on the biomechanical scheme of movement using the example of canoeing. The main focus of our research is on the study of the paddle grip and its impact on competitive performance. Among the methods of obtaining empirical data, the method of interviewing leading athletes who have achieved outstanding success in canoeing was used. In particular, the importance of such a skill as adjusting the grip of the oar, reducing or increasing it depending on the characteristics of the distance, the tactics of competitive wrestling is emphasized. It is also emphasized that the formation of such a sensation as the feeling of water is closely related to the width of the grip of the oar. The article provides a number of recommendations and tips on how to choose the right paddle grip. Leading athletes also emphasized the crucial role of the paddle grip in ensuring the effectiveness of the biomechanics of motor action in athletes specializing in canoeing. You can increase the feel of the water by reducing the width of the oar grip. As the rower’s skill increases, the width of the oar grip can be gradually increased until the technique of performing the stroke is at its highest efficiency. Leading athletes emphasize an individual approach to choosing the width of the oar grip, with important factors being physical qualities (shoulder girdle strength), anthropometric indicators, the rower’s level of training, etc.